2014
DOI: 10.3329/jbsa.v24i1.19794
|View full text |Cite
|
Sign up to set email alerts
|

Induction characteristic of general anaesthesia in children- a comparative study between sevoflurane and halothane

Abstract: Background Inhalational induction of anaesthesia remains of fundamental technique in paediatric anaesthesia. Halothane used most frequently for inhalational induction in children. Halothane is not an ideal induction agent because of its potential to cause bradycardia, hypotension and ventricular ectopy. The pleasant nonpungent order of sevoflurane, faster induction of anaesthesia and stable vital signs during induction suggest that it may be a suitable alternative to halothane for use in paediatric anaesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…An increase in MAP was observed in both the groups after intubation although it was not found to be statistically significant. Wadud et al 22 in a study reported significant decrease in MAP in halothane group, while no significant changes were observed in sevoflurane group. The hemodynamic results in the current study demonstrated that the stability of HR provided by sevoflurane was desirable as it neither increased the myocardial oxygen consumption nor decreased the time available for myocardial perfusion.…”
Section: R Esultsmentioning
confidence: 89%
See 1 more Smart Citation
“…An increase in MAP was observed in both the groups after intubation although it was not found to be statistically significant. Wadud et al 22 in a study reported significant decrease in MAP in halothane group, while no significant changes were observed in sevoflurane group. The hemodynamic results in the current study demonstrated that the stability of HR provided by sevoflurane was desirable as it neither increased the myocardial oxygen consumption nor decreased the time available for myocardial perfusion.…”
Section: R Esultsmentioning
confidence: 89%
“…In contrast, a study conducted by Shareena et al 19 reported a significant difference in the mean elevated HR between halothane and sevoflurane groups during induction. Wadud et al 22 reported a significant reduction in the HR in halothane group, whereas no changes were noted in sevoflurane group during the induction period. An increase in MAP was observed in both the groups after intubation although it was not found to be statistically significant.…”
Section: R Esultsmentioning
confidence: 95%